Directed evolution: tailoring biocatalysts for industrial applications. (December 2013) - Kumar, Ashwani; Singh, Suren
Abstract : Current challenges and promises of white biotechnology encourage protein engineers to use a directed evolution approach to generate novel and useful biocatalysts for various sets of applications. Different methods of enzyme engineering have been used in the past in an attempt to produce enzymes with improved functions and properties. Recent advancement in the field of random mutagenesis, screening, selection and computational design increased the versatility and the rapid development of enzymes under strong selection pressure with directed evolution experiments. Techniques of directed evolution improve enzymes fitness without understanding them in great detail and clearly demonstrate its future role in adapting enzymes for use in industry. Despite significant advances to date regarding biocatalyst improvement, there still remains a need to improve mutagenesis strategies and development of easy screening and selection tools without significant human intervention. This review covers fundamental and major development of directed evolution techniques, and highlights the advances in mutagenesis, screening and selection methods with examples of enzymes developed by using these approaches. Several commonly used methods for creating molecular diversity with their advantages and disadvantages including some recently used strategies are also discussed.